2013
DOI: 10.1371/journal.pone.0053680
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Allergy from Pollen to Clinical Symptoms

Abstract: Allergy to citrus fruits is often associated with pollinosis and sensitization to other plants due to a phenomenon of cross-reactivity. The aims of the present study were to highlight the cross-reactivity among citrus and the major allergenic pollens/fruits, throughout clinical and molecular investigations, and to evaluate the sensitization frequency to citrus fruits in a population of children and adults with pollinosis. We found a relevant percentage of sensitisation (39%) to citrus fruits in the patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
(62 reference statements)
3
21
2
3
Order By: Relevance
“…Additionally, oropharyngeal symptoms were observed in 41.7% of orange GRP‐sensitized patients in this study. In an Italian study, 39% of 72 children and young adults with pollinosis were found to be sensitized to citrus fruits . However, in the present study, sensitization to Bet v 1 homologs and profilin, which is related to pollen food‐associated syndrome, was observed in two and three of our patients, respectively.…”
Section: Discussioncontrasting
confidence: 81%
“…Additionally, oropharyngeal symptoms were observed in 41.7% of orange GRP‐sensitized patients in this study. In an Italian study, 39% of 72 children and young adults with pollinosis were found to be sensitized to citrus fruits . However, in the present study, sensitization to Bet v 1 homologs and profilin, which is related to pollen food‐associated syndrome, was observed in two and three of our patients, respectively.…”
Section: Discussioncontrasting
confidence: 81%
“…Iorio et al 5 found that C clementina pollen has profilins with DNA sequence homology to that of profilins from Malus domestica (apples) but not to profilins from C sinensis. 5 This parallels the findings in this case: the idea that C clementina expresses allergens not found in C sinensis or C reticulata (C clementina's ancestral species) but that are perhaps found in other plants.…”
supporting
confidence: 80%
“…Indeed phospholipases are known to be present in many other allergens including pollens and fungal allergens (75, 76) and therefore activation of this pathway may facilitate the allergenic process. By producing type 2 cytokines, CD1a-reactive lipid-specific T cells may lead to down-regulation of filaggrin and anti-microbial peptide expression and thus compound physical and antimicrobial barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%